The cytoplasmic domain of the human T-cell leukemia virus type I envelope can modulate envelope functions in a cell type-dependent manner. - Pique, C (1993)
C-terminal truncations of the human T-cell leukemia virus type I envelope affected the intracellular maturation and syncytium formation in a cell type-dependent manner. The intracytoplasmic domain appears dispensable for syncytium formation, but its truncation can modulate the envelope functionality in some cell types.